Evaluación de los niveles de iluminación y su incidencia en la capacidad visual de los trabajadores de las áreas de tornos convencionales y tornos CNC de la empresa Servisilva Cia ltda. Ubicada en la ciudad de puerto francisco de Orellana periodo 2016. Propuesta de mejora de iluminación. - Montes Vega, Klever Saúl (2017)
The purpose of this research work arise of the necessity to maintain a uniform lighting environment in the lathe area for non-compliance with 5CT by clause 10.14.1. The American Petroleum Institute (API), which establishes at least 500 lux. and also the Ecuadorian health and safety regulations through executive decree 2393 art 56 To maintain the visual health care of workers. the research objective is evaluate the lighting level which did do made a direct measurement in the conventional lathes area and CNC lathes area which the lighting levels are less to 500 lux. this can cause different effects on the product and the workers health. In the analysis some research techniques were used such as: the interview and the direct measuring to obtain the data in order to evaluate and compare them according with the applicable standards. In conclusion the lightning not is enough for the activity that realize and is recommended to apply the recommended proposal to maintain a uniform lighting environment workstation The proposal was carried out through Lumenes method which help us to calculate the numbers of necessary luminaries depending on the area´s size, the height of the work plane, and the height where the luminaires are suspended. The lightings were chosen by means of a cost benefit analysis, maintaining a level of saving electrical and investment where the best option was chosen within a variety of analyzed luminaries.